Angel and the Badman: Mockingjay, Spectre, and Choosing Sides in War Movies. (2nd July 2016) - Beck, Bernard
Abstract : Recent films in the James Bond series and the Hunger Games series have taken entertaining and sentimental versions of stories about violence in the struggle between the established state and rebels against the state. The craft of the moviemaker lends heroic stature to one side in this fight, thus justifying the use of violence. In these movies, different sides are made to seem virtuous. In the James Bond movies, the defenders of the established order are the good guys. In the Hunger Games movies, the rebels trying to bring down the established order are the good guys. Our ambivalence about violence, morality, and inequality in general is not resolved, but only masked by the needs of entertaining story telling.